Phosphorite in the production of azevém as soil coverage in winter in Cerrado Mineiro (Research, Society and Development, 2020)
The aim of this study was to evaluate the effects of phosphorite on the production of ryegrass as ground cover in winter in the Cerrado Mineiro. The study was conducted at the State University of Minas Gerais, Passos Academic Unit. The experiment was conducted in a randomized block design, with two sources of phosphorus P (MAP - monoammonic phosphate and phosphorite) and control (without fertilization), with seven replications, totaling 21 plots. The ryegrass was conducted in the field until the full flowering stage, when height, dry mass yield of the hoot part and macro and micronutrient contents were measured. From these data, the accumulated nutrient values were calculated. The data were submitted to ANOVA and when significant, the means were compared using the Tukey-Kramer test (P